Automated hydraulic systems for transport of fish from fishing gears with vacuum fishpump - Vasily V. Kudakaev; Timofey P. Karpelev; Anatoly N. Boitsov (Известия ТИНРО, 2016)
New techniques of fish tranport from fishing gears aboard is proposed for a case of mixed aggregations of chub mackerel and japanese sardine. These species resume their mass migration to the Russian waters since 2014. Submersible impeller pumps with hydraulic power drive are used usually for catch transport aboard in the world practice of purse seining of mackerel. However, this technique is unsuitable for mixed aggregations of mackerel and sardine because the impeller pump could damage the sardine. Applicability of the vacuum and waterjet pumps for this case is considered. The vacuum fish pump TransVac was designed in 1982, initially for transfer of damage-sensitive fish from fishing vessel to shore fish processing plant, and the waterjet fish pump SilkStream was designed in 1988 for transfer of alive fish and later was adapted for fish transport aboard from trawl and seine nets. Both types of fish pumps are recommended for the medium- and large-capacity fishing vessels working with the mixed aggregations of sardine and mackerel. Using of these pumps together with freezing equipment allows to avoid losses in quality of catch.